Neutrophil-to-lymphocyte ratio is increased in patients with rheumatic mitral valve stenosis? - Akboğa, Mehmet Kadri (Anatol J Cardiol, 2015)
OBJECTIVE: The role of systemic and chronic inflammatory processes in the pathophysiology of rheumatic heart valve disease is well known. The neutrophil-to-lymphocyte ratio (NLR) was shown to be an indicator of systemic inflammation. In this study, we aimed to investigate relationship between NLR as a marker of systemic inflammation and rheumatic mitral valve stenosis (RMVS). METHODS: This is a retrospective study. Among patients who underwent transthoracic echocardiography between January 2008-March 2013, 314 patients with RMVS were included retrospectively in the study. The control group included 57 healthy persons who underwent transthoracic echocardiography during the study period. Basal characteristics and NLR were compared between the two groups. Independent predictors of RMVS were determined by logistic regression analysis. RESULTS: Basal characteristics were similar among the groups (age, 50.2±14.2 vs. 49.2±13.0, p=0.60). The NLR was significantly higher in patients with RMVS [2.9 (0.6-13.0) vs. 2.1 (0.7-5.8), p<0.001]. Besides, C-reactive protein (CRP) was also higher in the RMVS group [5.99 (0.3-23.7) vs. 2.98 (0.6-6.3), p=0.001]. In the regression analysis, NLR (OR: 2.24, p=0.04), CRP (OR: 1.34, p=0.03), and left atrial diameter (OR: 1.21, p=0.001) were independent predictors of RMVS. In the correlation analysis, there was a significant positive correlation between NLR and CRP (r=0.43, p<0.001). CONCLUSION: We found that NLR was significantly increased in RMVS. Furthermore, NLR was an independent predictor of the presence of RMVS in our study population. According to these findings, NLR can be used as a predictor of RMVS. Since it is an easily available and cheap method, it can easily be used in daily clinical practice. Increased NLR can also be a sign of ongoing chronic inflammation in patients with RMVS.